Jsou změny krevního obrazu použitelným ukazatelem velikosti dávky azathioprinu? - Kojecký, Vladimír; Matouš, Jan; Zádorová, Zdena; Kianička, Bohuslav; Hep, Aleš (Vnitrni lekarstvi, 2020)
INTRODUCTION: The 6-thioguanine nucleotide (6-TGN) level, may be used to estimate dose-adequacy of azathioprine (AZA) therapy. 6-TGN test is not commercially available. The aim of the study was to determine whether a blood cell changes correlate also with the dose of AZA and may serve as a predictor of the dose adequacy (for MCV > 6 fl). METHODS: Retrospective, multicentre study in subjects with IBD treated with azathioprine. Demographic data, leukocyte, platelet counts, erythrocyte (MCV) and thrombocyte (MPV) volume, azathioprine dose, inflammatory activity in the 3rd, 6th and 12th months of treatment and presence of sideropenia were recorded. RESULTS: 103 subjects analysed. To increase the MCV by 6 fl, the AZA dose above 2 mg/kg is needed (p = 0.04). The MCV increases within 165 days (95% CI, 154-181 days, p = 0.002). Sideropenia has no impact on the MCV change. Number of leukocytes and thrombocytes decreases during treatment (p < 0.001). Change in their number as well as MPV, does not correlate with MCV change and is not affected by activity of the inflammation. CONCLUSION: The MCV dynamics (> 6 fl within 6 months) is the only relevant indicator during AZA treatment. Changes in the number of leukocytes, platelets and their volume can not be used to assess the sufficiency of the AZA dose. Sideropenia has no impact on the dynamics of MCV.
Keywords: azathioprine; idiopatické střevní záněty; blood test monitoring; inflammatory bowel diseases; azathioprin; Inflammatory Bowel Diseases; merkaptopurin; lidé; Humans; Retrospective Studies; Mercaptopurine; imunosupresiva; Azathioprine; Immunosuppressive Agents; retrospektivní studie